Keeping it INTACT: Holistic Development of Drug Addiction Counsellor Competency - Abd Halim, Mohd Hussin (2014)
This paper discusses the holistic development of drug addiction counselor competency based on a model known INTACT which was an outcome of a research project conducted by iire author. INTACT model proposed the development of counselors competency based on four transdisciplinary foundations: understanding addiction, treatment knowledge, application to practice, and professional readiness. This model is also supported by eight dimensions of addiction counseling namely: Clinical Evaluation, Treatment Planning, Referral, Service Coordination, Counseling, Client, Family and Community Education, -Documentation and Professional and Ethical Responsibilities. Integrated Addiction Counseling Training (INTACT) Competency Models seem to be able to fulfil the skills required for the treatment and rehabilitation process in Malaysia as it encompasses across discipline and able to detail out competencies needed for substance abuse related problems in a holistic environment. This model of training consists of dimensions of competency as proposed by ACCM, in combination with psycho-spiritual components adhering to the licensing requirements of the Board of Counselors, Malaysia. INTACT Model consist of three majoi components namely : the components of behavioral science and social psychology, covering the dimensions of transdisciplinary foundation and dimensions of practice, components of counseling skills, and components of psycho-spirituality in addiction. This multi-disciplinary knowleJge and skill base needs to be coupled with hands-on experience providing adequate opportunity to apply theoretical principles to practice